THE SUNNIS OF THE PROPHET DENOUNCED READING IN THE UPBRINGING AND METHODS OF CONFRONTATION (Islamic Sciences Journal, 2023)
In the name of of Allah the MercifulPraise be to God, Lord of the worlds, and prayers and peace be upon Muhammad - may God bless him and grant him peace - and upon all God and his companions.And after:The research, entitled (Deniers of the Prophetic Sunnah, Reading in Genesis and Methods of Confrontation), has spread about some The ignorant of some suspicions about the authenticity of the Sunnah and its position, so we did this research to respond to the suspicions and some of the denials around whom suspicions were held to challenge the Prophet’s Sunnah and disrupt its role in the statement, guidance and legislation, echoing their ancestors from the people of aberration and delusion. So I saw that it is necessary to contribute, even a little, to defending the Sunnah of the Messenger of God, peace and blessings be upon him, through an analytical reading of the origins of the prophets of the Sunnah of the Prophet, past and present, to determine the nature of these deniers, and the factors of their appearance and their connections to the enemies of Islam, then after that I tried to put effective solutions through A number of ways that contribute to confronting the deniers of the Sunnah. I do not want through this research inductive historical study, as many writers and researchers preceded it, but I tried to address their origins and the ways in which they were confronted with analytical reading, which I did not precede, according to my reading and follow-up, because previous studies neglected to explain ways to confront the deniers of the year, and focused on the suspicions and response to them, without Pay attention to the mechanisms of your confrontation to prevent them from spreading among our societies
Keywords: Deniers of the year reading, confrontation,Origination brief history